CARACTERIZAÇÃO DE ADULTAS COM LOMBALGIA CRÔNICA PRIMÁRIA NÃO PRATICANTES DE EXERCÍCIOS FÍSICOS EM SÃO LUÍS - MA - PRAZERES, Jaidilene de Jesus Soares (2022)
Introduction: Primary chronic low back pain (PCL) represents up to 90% of low back pain cases. It is defined as pain or discomfort located below the costal margin and above the inferior gluteal folds, with no defined etiology. Objective: To characterize adults with PCL who do not practice physical exercises in São Luís, Maranhão. Materials and Methods: Inclusion criteria: women; between 20 and 50 years; self-reported PCL; without regular physical activity for at least three months; no neuropathies or fibromyalgia. The sample consisted of 35 adults with a mean age of 32.91 years (standard deviation ± 7.88). The following assessments were performed: a)anthropometric data (scale, body mass and stadiometer, height) and education level; b)visual analogue scale (pain intensity); c)Tampa scale (kinesiophobia); d)Roland Morris questionnaire (functional disability); e)goniometry (flexibility of the lumbar spine and hip); f)stork stall test (static equilibrium). In the descriptive analysis, absolute values, mean, standard deviation and frequency distribution were presented; in the inferential, a Spearman correlation matrix was performed between: age,BMI, pain intensity, kinesiophobia, functional disability and balance. Results: In BMI (27.61 ± 17.35) most of the sample was classified as normal weight (n = 13), followed by grade 1 obesity (11), overweight (8), grade 2 obesity (2) and grade 3 (1). In terms of schooling, most had higher education (13) and complete high school (12), followed by incomplete higher education (6), incomplete high school (2) and incomplete master's degree (2). In terms of pain intensity (52.71 ± 18.95 millimeters) the majority had moderate pain (17), followed by strong (13) and mild (5). Most women (29) did not present functional disability (9.77 ± 5.02). In terms of kinesiophobia (38.49 ± 7.52), most of them had a moderate degree (24), followed by mild (10) and severe (1). In the range of motion (ROM) of the spine and hip, all the volunteers had the angles below the reference values: spine; flexion (8.79 ± 9.04), extension (24.52 ± 6.78), lateral flexion to the right (25.32 ± 5.51) and left (24.76 ± 5.01); hip; flexion (59.80 ± 19.85), extension (7.56 ± 2.54), internal (26.13 ± 7.95) and external (24.89 ± 8.05) rotation. In static balance (4.57 ± 5.6 seconds) most were classified as beginner (17), followed by advanced beginner (15), intermediate (2) and advanced (1). There was a significant correlation between kinesiophobia and functional disability (ρ = 0.60, p < 0.05) and between BMI and pain intensity (ρ = 0.55, p < 0.05). Conclusion: Most women with PCL who did not practice physical exercises: were classified as having normal weight, followed by grade 1 obesity and overweight; had higher education and completed high school; moderate pain followed by severe, without functional disability, moderate kinesiophobia, balance at initial levels and flexibility of the spine and hip below those indicated. The significant correlations support part of the fear- avoidance model, in which greater fear of movement leads to greater disability and may emphasize the importance of physical exercise to improve body composition, in addition to other positive effects in the management of PCL.